Does what you get depend on who you are with? Effects of student composition on teaching quality. (February 2021) - Fauth, Benjamin; Atlay, Cansu; Dumont, Hanna; Decristan, Jasmin
Abstract: This study focuses on the association between classroom composition characteristics and teaching quality, with the aim of understanding the role of teaching quality as a mechanism underlying compositional effects. We examine how teaching quality is associated with the student body that is taught. Multilevel analyses of a sample of 1, 070 3rd graders have indicated that cognitive and motivational composition of the classroom had an association with the classroom management dimension of teaching quality, whereas sociocultural composition was not associated to any of the teaching quality dimensions rated by the students. Correlations at the classroom level have also pointed at a relationship between the teachers' and observers' ratings of classroom management and the composition of general cognitive abilities and interest. We suggest that these findings also have implications for the theoretical conceptualization and the empirical assessment of teaching quality. Highlights: We examined effects of student composition on teaching quality. Students' cognitive abilities and interest were related to classroom management. Similar effects when teachers and external observers rated teaching quality. Student body may be an important situational factor for teaching quality.